UJI AKTIVITAS DIURETIK EKSTRAK AKAR AREN (Arenga pinnata (Wurmb.) Merr.) TERHADAP TIKUS PUTIH GALUR WISTAR (Rattus Norvegicus) DENGAN PEMBANDING FUROSEMID - Ahmad Zainudin; Uswatun Hasanah; Yan Reiza Pemana (poltekkes kemenkes mataram, 2015)
Abstract: Background: Traditional medicine herb ingredient or ingredients are derived from growing-plants, animals, and minerals, galenik preparations or mixtures of these materials that are passed down through generations has been used for the treatment of. Sugar Palm roots (Arenga pinnata (Wurmb.) Merr.) nutritious as deciduous deciduous urine and menstruation. The purpose of this research is to know the diuretic activity of root extract of white rat strain aren wistar (Rattus norvegicus), and knowing the optimal levels of root extract of Palm that has a diuretic activity of white rats wistar strain. As many as 25 test animal's tail is divided into 5 groups: control group i.e treatment of negative (aquadest), a positive control group (furosemid suspension), group root extract aren 100 mg/kg, group root extract aren 200 mg/kg and groups of Palm root extract 300 mg/kg. Diuretic effect of testing done by looking at the volume of urine is issued for 18 hours. The results showed issuing Palm root extract during the time of observation going on increased volume of urine. Data were analyzed with spss 16, unlike any real treatment tested by one way ANOVA. Increased concentrations of root extract aren showed better results. Based on these results, it was concluded that root extract has a diuretic effect of areca palm (p < 0.05) and optimal levels of root extract of Palm that has a diuretic activity of white rats wistar strain is 300 mg/kg.